2008
DOI: 10.1080/09540120701426524
|View full text |Cite
|
Sign up to set email alerts
|

Experience of hepatitis C testing among injecting drug users in Sydney, Australia

Abstract: Testing injecting drug users (IDUs) for HIV and hepatitis C virus (HCV) provides a useful opportunity for health promotion, risk-reduction assessment and counselling, and increases opportunities for treatment assessment, yet little is known about IDUs' experience of testing. This study aimed to examine the experiences of testing among IDUs recruited through primary healthcare and drug treatment services. Almost all the 229 participants recruited had been previously tested for HIV (96%) and HCV (97%), a median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 19 publications
3
16
0
1
Order By: Relevance
“…Free HCV testing at methadone clinics eliminates a potential barrier to screening associated with clinic-based testing. One study showed IDUs preferred methadone clinics more than general medicine clinics or specialized clinics as locations for HIV and HCV testing [23]. Our research suggests that routine HIV/HCV screening at methadone clinics can provide a successful model for scaling up HIV/HCV prevention and control programs.…”
Section: Discussionmentioning
confidence: 87%
“…Free HCV testing at methadone clinics eliminates a potential barrier to screening associated with clinic-based testing. One study showed IDUs preferred methadone clinics more than general medicine clinics or specialized clinics as locations for HIV and HCV testing [23]. Our research suggests that routine HIV/HCV screening at methadone clinics can provide a successful model for scaling up HIV/HCV prevention and control programs.…”
Section: Discussionmentioning
confidence: 87%
“…First, since the study did not conduct HCV serologic testing, all data on HCV are self-report, including history of testing and HCV status. Self-report data for HCV status may be subject to social desirability and recall biases, but studies on HCV self-report data among IDUs indicate that large proportions know their true HCV serologic status – particularly IDUs who self-report being HCV positive (Day et al, 2008; Hagan et al, 2006; O’Keefe, Aitken, Higgs, & Dietz, 2013). In the present study, IDUs who did not know their status or had never been tested were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns related to stigma and to access to care were reported as important factors for decision-making. [67][68][69][70][71][72][73][74] A survey of 15 patients commissioned by the task force generally reinforced these findings and found that participants placed equal value on the benefits and harms of screening. 20 Reduced mortality was perceived as a very important benefit, and concerns were noted about stigma and psychological adverse events from positive results of screening tests.…”
Section: Patient Values and Preferencesmentioning
confidence: 91%
“…The screening review 16 found moderate-to low-quality evidence from 12 observational studies, [67][68][69][70][71][72][73][74] which reported on patient preferences and values related to the decision to be screened for HCV. Findings were highly variable in terms of patient preferences related to screening and there was a high level of uncertainty about the value that patients place on the clinical outcomes considered in the review.…”
Section: Patient Values and Preferencesmentioning
confidence: 99%